2018
DOI: 10.1186/s12986-018-0245-3
|View full text |Cite
|
Sign up to set email alerts
|

Fructo-oligosaccharides and glucose homeostasis: a systematic review and meta-analysis in animal models

Abstract: The aim of this systematic review was to assess the effect of fructo-oligosaccharide supplementation on glucose homeostasis. The search process was based on the selection of publications listed in the Pubmed-Medline database until April 2016 to identify studies evaluating the impact of short-chain fructo-oligosaccharides or oligofructose on glucose homeostasis. Twenty-nine trials were included in the systematic review and the meta-analysis was performed on twelve of these papers according to the inclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…Also, other studies using one specific fibre did not show very pronounced metabolic effects as reviewed by Canfora et al (2019). Although some studies using specific prebiotic supplements showed promising metabolic effects (Dehghan et al, 2016;Dehghan et al, 2013;Rao et al, 2019), the message may be that it is important to keep the diversity of SCFA-producing bacteria high by providing different microbial substrates instead of stimulating one specific SCFA producing genus (Le Bourgot et al, 2018;Rao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, other studies using one specific fibre did not show very pronounced metabolic effects as reviewed by Canfora et al (2019). Although some studies using specific prebiotic supplements showed promising metabolic effects (Dehghan et al, 2016;Dehghan et al, 2013;Rao et al, 2019), the message may be that it is important to keep the diversity of SCFA-producing bacteria high by providing different microbial substrates instead of stimulating one specific SCFA producing genus (Le Bourgot et al, 2018;Rao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fructo-oligosaccharides (FOS) are soluble dietary fibers, and as prebiotics, they are selectively fermented by specific gut microbiota [ 10 ]. FOS are naturally present in select fruits and vegetables or produced from beet sugar, frequently used to replace sugars in the formulation of low-sugar food [ 11 ]. Animal studies indicate FOS augments (poly)phenolic metabolites generation: adding FOS to a 4-week intake of (poly)phenol concentrate from apple pomace enhanced the hydrolysis of quercetin 3- O -glucoside in rats [ 12 ]; and adding FOS to a 4-week strawberry feeding study enhanced urolithins production in rats [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This latter observation may in fact be interpreted in a quite different way. It could well be that the bulk of the microbiota of faecal origin does not reflect the nature of the microbes that are important for the host [except, perhaps, for the recovery of carbon derived metabolites (Louis and Flint, ; Le Bourgot et al ., )], in particular via key interactions with cell surfaces. As a matter of fact, cell surfaces are substantially modified by glycosylation.…”
Section: Genomes and Evolution: The Gut Microbiota Of Man And Great Apesmentioning
confidence: 99%